2015
DOI: 10.1038/ejcn.2014.289
|View full text |Cite
|
Sign up to set email alerts
|

The role of acetic acid on glucose uptake and blood flow rates in the skeletal muscle in humans with impaired glucose tolerance

Abstract: In individuals with IGT, vinegar ingestion before a mixed meal results in an enhancement of muscle blood flow, an improvement of glucose uptake by the forearm muscle and a reduction of postprandial hyperinsulinaemia and hypertriglyceridaemia. From this point of view, vinegar may be considered beneficial for improving insulin resistance and metabolic abnormalities in the atherogenic prediabetic state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 49 publications
(94 reference statements)
1
32
1
Order By: Relevance
“…The increases in PPG in the first hour following vinegar supplementation in this study was contrary to the lowering of first phase PPG by vinegar in healthy volunteers [23,24]. In a more recent study, vinegar consumption led only to a small reduction in arterial PPG of only around 6% over a 3-h period in a T2D population [37], whereas no effect in PPG was observed in IGT individuals [38]. The study in T2D however did observe a significant reduction in arterial plasma insulin and an increase in peripheral glucose uptake, despite no changes in blood flow, suggesting an improvement in insulin sensitivity.…”
Section: Human Dietary Intervention Trials Of Vinegar or Acetic Acid contrasting
confidence: 93%
See 1 more Smart Citation
“…The increases in PPG in the first hour following vinegar supplementation in this study was contrary to the lowering of first phase PPG by vinegar in healthy volunteers [23,24]. In a more recent study, vinegar consumption led only to a small reduction in arterial PPG of only around 6% over a 3-h period in a T2D population [37], whereas no effect in PPG was observed in IGT individuals [38]. The study in T2D however did observe a significant reduction in arterial plasma insulin and an increase in peripheral glucose uptake, despite no changes in blood flow, suggesting an improvement in insulin sensitivity.…”
Section: Human Dietary Intervention Trials Of Vinegar or Acetic Acid contrasting
confidence: 93%
“…The study in T2D however did observe a significant reduction in arterial plasma insulin and an increase in peripheral glucose uptake, despite no changes in blood flow, suggesting an improvement in insulin sensitivity. In contrast, other studies have shown vinegar to increase blood flow in nondiabetic, impaired glucose-tolerant individuals [38] and in nondiabetic postmenopausal women [39]. The lack of this effect in diabetics is probably indicative of their compromised peripheral vascular elasticity response.…”
Section: Human Dietary Intervention Trials Of Vinegar or Acetic Acid mentioning
confidence: 83%
“…In particular, we found that the increased acetic acid correlated with resistance to diabetes. Acetic acid, or vinegar, has been shown to improve insulin resistance and metabolic abnormalities during pre-diabetes in human clinical trials (Mitrou et al, 2015). Although we correlate the lack Figure 6 NOD mice given antibiotics carry a microbiota that produces fewer short-chain fatty acids.…”
Section: Discussionmentioning
confidence: 72%
“…The antibiotic-induced diabetes correlated with changes to the microbiome characterized by reduced diversity, enriched pathobionts, depletion of protective microbes and overall changes to the metagenome, including several gene clusters involved in metabolism. Similarly, we found that antibiotic treatment resulted in reduced microbial short-chain fatty acid (SCFA) metabolites, which are known to protect against diabetes (Al-Lahham et al, 2010;Mitrou et al, 2015). Finally, to try and overcome the diabetogenic effects of the microbiome, we administered VSL#3 probiotics to NOD mice and found they had no effect on diabetes onset due to their poor colonization of the gut.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the reduction of postprandial glucose affected by vinegar in high GI meals is not observed for low GI meals (Liatis et al., ). However, vinegar ingestion with both high‐ and even low‐GI meals does improve insulin sensitivity, independent of blood glucose level, as glucose uptake was enhanced after both meal types when vinegar was also ingested (Mitrou et al., ). Indeed, even the improvement by vinegar consumption of insulin sensitivity alone is noteworthy, particularly in insulin‐resistant (prediabetic) subjects, as trials have demonstrated that slowing the progression to diabetes in high‐risk individuals and improving their insulin sensitivity may increase the probability that such individuals may revert to a normal, glucose‐tolerant state over time (Johnston & Gaas, ).…”
Section: Beneficial Effects Of Aab‐fermented Productsmentioning
confidence: 99%